Microstructure evolution during high pressure torsion of AZ80 magnesium alloy - Arpacay, Dogan; Yi, Sangbong; Janecek, Milos; Bakkaloglu, Adem; Wagner, Lothar (TRANS TECH PUBLICATIONS LTD, 2008)
The microstructure evolution during high pressure torsion and its influence on the mechanical properties of AZ80 magnesium alloy is presented in this study. Significant grain refinement was observed after high pressure torsion. while the homogeneity of the grain structure increases with the number of revolutions. Grain size decreases to about 50 nm after 15 revolutions. The microhardness profiles measured at through-thickness and through-width directions show no significant variation at different positions of the sample. Moreover. the negligible effect of the revolution number on the microhardness value was observed.
Keywords: severe plastic deformation; high pressure torsion; magnesium; microstructure; GRAIN-REFINEMENT; DEFORMATION; SUPERPLASTICITY; ALUMINUM; ECAP; Science & Technology - Other Topics; Materials Science